Sistem Pendukung Keputusan Pemilihan Asisten Dosen Menggunakan Metode SAW - Triana Elizabeth (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
The process of selecting the teaching assistant starts with announcements on the campus web. The requirement is to have an A and at least on 3rd semester. Because the selection of lecturer assistant lecturers is only based on the value of the student's courses, there are a number of lecturers and students in the class who feel the teaching assistant in the course does not have a positive impact on lectures. This is because the students who are teaching assistants are not active, it is difficult to communicate with juniors, and there is some material that they have not mastered so it is difficult to explain it to juniors. Therefore, we need a decision support system that can help academics make decisions about who students they will choose as teaching assistants and help the head of the informatics engineering study program to get information about students who have been teaching assistants. This decision support system applying Decission Fuzzy Multiple Attribute Making (FMADM) and Simple Additive weighting method (SAW). This decision support system design uses the Netbeans IDE 8.2 application and MySQL as the database.